2013
DOI: 10.1111/ced.12072
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset pretibial recessive dystrophic epidermolysis bullosa

Abstract: Pretibial epidermolysis bullosa (EB) is a rare form of localized dystrophic EB, characterized by recurrent blistering and scarring plaques occurring predominantly in the pretibial area. In most cases, nail dystrophy, especially of the toenails, is also present. Often there are no clinical abnormalities at birth, and the disorder may only appear after several years. We report a patient who developed symptoms in his fifth decade. Genetic testing identified compound heterozygosity for two pathogenic mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 7 publications
2
13
1
Order By: Relevance
“…In the present case, the eruptions were not fully restricted to the pretibial region but were also observed on the calves and elbows. Such distribution of extended lesions to regions other than the pretibial have been reported in previous cases of DEB, pretibial …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the present case, the eruptions were not fully restricted to the pretibial region but were also observed on the calves and elbows. Such distribution of extended lesions to regions other than the pretibial have been reported in previous cases of DEB, pretibial …”
Section: Discussionsupporting
confidence: 83%
“…Such distribution of extended lesions to regions other than the pretibial have been reported in previous cases of DEB, pretibial. [2][3][4][5] Gene analysis revealed that the present patient was a compound heterozygote with a premature termination codon (PTC) mutation (p.R1933X) and a splice site mutation (c.6348+1G>A) that generated two aberrant in-frame transcripts in COL7A1. The p.R1933X mutation has already been reported to be a recurrent mutation of recessive DEB, including the Hallopeau-Siemens type, and a de novo p.R1933X mutation has also been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pruritus is common and there is a clinicopathological overlap with epidermolysis bullosa pruriginosa. 6 Delayed diagnoses are common as clinical features can be atypical sometimes resulting in multiple ineffective therapies. 5,7 Clinical mimickers include localized bullous and lichenoid dermatoses, and patients have also been misdiagnosed as prurigo nodularis and even dermatitis artefacta.…”
Section: Editormentioning
confidence: 99%
“…2 However, there are few cases described in the literature of tattoo pigment in the sentinel lymph nodes of melanoma patients and represents a clinical challenge. [3][4][5][6] The tattoo ink particles, in their natural evolution, initially are in large phagosomes within the cytoplasm of phagocytic cells and keratinocytes. 5 At 2 months-40 years, ink particles are only found in dermal fibroblasts surrounded by a network of connective tissue.…”
Section: Editormentioning
confidence: 99%